Plasma autoantibodies in patients with Affective and Schizophrenic Spectrum Disorders - Christian Scheiber; Alexander Dulcovic; Karl Bechter; E. Marion Schneider (Journal of Affective Disorders Reports, 2023)
Background: A number of results emphasize autoimmune characteristics in psychiatric diseases, including Affective (AF) and Schizophrenic (SZ) Spectrum Disorders. Study subjects and methods: In this study, serum/plasma samples of n=34 AF (ICD-10 F30-F33) and n=47 SZ (ICD-10 F20-F25) patients, as well as n=10 healthy controls (HDs), were tested for autoantibodies directed against cytokines and different Type I, Type II and Type III interferons using Luminex® technology. Results: Significant amounts of autoantibodies against cytokines were found. Specifically, IFN- λ (AF n=4, SZ n=4), IFN- ω (AF n=2, SZ n=3), and TNF-α (AF n=4, SZ n=1) were selectively increased. Conclusion: The results support autoimmune dysregulation as a contributing factor in psychiatric diseases. Interestingly, the detected patterns were not different between AF and SZ patients. The humoral immunity against common virus infections such as EBV, CMV, HSV-1 and HHV-6 is currently tested.